Best Customer Services among the E-Commerce Websites – A Predictive Analysis (International Journal of Engineering and Computer Science, 2018)
Online shopping websites have become popular as they allow customers to purchase the products easily from home. These websites requests the customers to rate the quality of the products. To enhance the quality of the products and services these reviews provides different features of the products. In order to buy a product a customer has to go through large number of reviews, which is quite hard for the customers as well as the marketers to maintain, keep track and understand the views of the customers for the products. In this project I have designed a consolidated website where I have the comparison data about the e-commerce website services such as Price, cash on delivery, Product replacement etc., and gave the predictive result about the shopping website which gives the best cutomer services. This can ease the purchasing time of the customer instead of comparing the shopping websites to review about the product and finding the best e-commerce website to purchase the product.